Salmonella cross-contamination in swine abattoirs in Portugal: Carcasses, meat and meat handlers - Eduarda Gomes Neves (2012)
In this study the occurrence of Salmonella in swine, pork meat and meat handlers along with their clonal relatedness is evaluated at abattoir level. Samples from the lymph nodes, carcass surface and meat of 100 pigs and 45 meat handlers were collected in eight abattoirs (July 2007-August 2008). Salmonella isolates were serotyped and genotyped by pulsed-field gel electrophoresis (PFGE). From the pigs tested, 42 produced at least one positive sample. A relatively high frequency of Salmonella occurrence was found in the ileoceacal lymph node samples (26.0%), followed by carcass (16.0%) and meat samples (14.0%). However, ileoceacal lymph nodes that test positive for Salmonella are not found to be a predictor of positive test results further on in the process. Besides the slaughterhouse environment, meat handlers were identified as a possible source of subsequent contamination, with 9.3% of the sample testing positive. Diverse Salmonella enterica serotypes were detected, mainly S. Typhimurium and the monophasic variant S. 4,[5],12:i:-, but also S. Derby, S. Rissen, S. Mbandaka, S. London, S. Give, S. Enteritidis and S. Sandiego, in total corresponding to 17 PFGE types. Our results demonstrate that besides a high level of Salmonella swine contamination at pre-harvest level, slaughtering, dressing, cutting and deboning operations are contributing to the occurrence of clinically relevant clones (e.g. S. Typhimurium DT104 and S. 4,[5],12:i:-) in pork products. This study also highlights the possibility of an ongoing Salmonella community being spread by abattoir workers.